Peningkatan Keaksaraan Awal dan Pengenalan Kemampuan Berhitung Dasar Anak Usia Dini dengan Menggunakan Model Maya Hasyim - Heni Nafiqoh; Ema Aprianti; Euis Eti Rohaeti (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2019)
AbstractThe objectives to be achieved through this research are to analyze and describe the implementation of the Maya Hasim implementation of the word through Kindergarten to improve the development of early literacy skills and basic counting. Results of the Maya Hasim application of words and their effects on Kindergarten. Drivers and obstacles to the application of Maya Hasim words in an effort to improve the development of early literacy skills and calculate the basis for children in Kober. The research method used is qualitative research with the consideration that the research subject is TK Tridaya Cimahi students. This study shows that the efforts of early literacy skills and basic counting through the application of the Maya Hasim  Hasim model were useful. Children can imitate what the teacher has shown and done. In order for children to emulate all the activities instructed by the teacher, the teacher must regulate the application of the Maya Hasim model in explaining their activities. The application of the Maya Hasim model is very influential on the concentration of children. The application of the model Maya Hasim makes children interested in learning, children will become more enthusiastic about learning. Keywords: Early Literacy and Basic Counting.           AbstrakTujuan yang ingin dicapai melalui penelitian ini adalah untuk menganalisa serta mendeskripsikan pelaksanaan penerapan maya hasim melalui TK untuk meningkatkan pengembangan kemampuan keaksaraan awal dan berhitung dasar. Hasil penerapan maya hasim dan pengaruhnya terhadap TK.  Pendorong dan penghambat  penerapan maya hasim dalam upaya peningkatan  pengembangan kemampuan keaksaraan awal dan berhitung dasar  bagi anak di TK. Metode Penelitian yang di gunakan Penelitian kualitatif dengan pertimbangan bahwa subjek riset adalah Siswa TK Tridaya Cimahi. Penelitian ini menunjukkan hasil bahwa upaya  kemampuan keaksaraan awal dan berhitung dasar  melalui penerapan model maya hasim. Anak dapat meniru apa yang telah ditunjukkan dan dilakukan oleh guru. Agar anak dapat meniru semua kegiatan yang diinstruksikan oleh guru, guru harus mengatur penerapan model maya hasim dalam menjelaskan kegiatannya. Penerapan model maya hasim sangat berpengaruh pada konsentrasi anak. Penerapan model maya hasim membuat anak tertarik untuk mengikuti pembelajaran, anak akan menjadi lebih antusias mengikuti pembelajaran.  Kata Kunci:  Keaksaraan Awal dan Berhitung Dasar.